Dose-Dependent Absorption Profile of Different Magnesium Compounds - Ates, Mehmet; Kizildag, Servet; Yuksel, Oguz; Hosgorler, Ferda; Yuce, Zeynep; Guvendi, Guven; Kandis, Sevim; Karakilic, Aslı; Koc, Basar; Uysal, Nazan (Biological trace element research, 2019)
Magnesium, one of the basic elements for the human body, is necessary for many physiological functions. Magnesium deficiency is widely observed as a result of the reduced nutrient content of foods, over-cooking, diseases, drugs, alcohol, and caffeine consumption. Taking a dietary supplement is necessary magnesium deficiency. It has been demonstrated that absorption of organic magnesium compounds is better than absorption of inorganic compounds. The aim of this study is to investigate transitions to tissues of different organic magnesium compounds in different doses and whether there is a difference in the organic acid–bounded compounds (magnesium citrate and magnesium malate) and the amino acid–bounded compounds (magnesium acetyl taurate and magnesium glycinate), associated with transition and bioavailability. In addition, the effects of split dosages of high doses in a high volume of solvent on tissue magnesium levels are being investigated, because galenic formulation problems are regarded to prepare convenient dosage that can be taken once a day. All magnesium compounds were administered as three different doses, 45, 135, and 405 mg/70 kg elemental magnesium, were given per orally to Balbc mice. In a second set of experiments, 405 mg/70 kg high dose was divided into two doses of 202.5 mg/70 kg each and administered every 12 h. Brain, muscle tissues, and serum magnesium levels measured in all experimental groups and control 24 h later. Brain magnesium levels were found increased in all magnesium acetyl taurate administered subjects. Magnesium citrate increased muscle and brain magnesium levels in a dose-independent manner. We showed that dividing high doses of daily administered magnesium compounds did not sufficiently increase tissue magnesium levels. Although passive paracellular mechanism by solvent drag is the main mechanism of Mg absorption, other factors (electrochemical gradient effects, transcellular transporter mechanisms, magnesium status) should be effective on our results. It is necessary for further research on long-term administration of different magnesium compounds and their effect on other tissues.